Effect of Volatile oil extracted from Citrus grandis yellow peel on growth of some food borne microorganisms - Ali, B. Z.; AL-Qaissi, E.; Mohammed, E. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study is conducted to investigate the effect of volatile oil extracted from the yellow peel of C. grandis fruits (Sindi) on growth of three bacterial species isolated from food samples , as well as A. flavus , and to check the possibility of using the volatile oils of this plant as a food preservative . Results showed a variation in the sensitivity of the bacterial isolates against the volatile oil which showed inhibitory effect on the growth of S. enteritidis and S. aureus with the increasing concentration of the volatile oils used in this studys , MIC for both bacteria was (0.12 , 1)% (v:v) respectively. Whereas , P. aeruginosa showed complete resistance to all treating concentrations used . Results of treating spore suspension of A. flavus with different concentrations of volatile oil showed also complete inhibition of germination at concentrations (0.12 , 0.25 , 0.5 , 1)%. Whereas lower concentrations (0.03 , 0.06)% delayed spore germination for (11) and (17) hrs after incubation respectively compared to the control treatment in which spores germination was within (6) hrs after incubation . Different concentrations of the volatile oil also affected the radial growth rate of A. flavus was colonies with the increasing concentrations . A complete inhibition of growth occurred at concentrations (0.12 , 0.25 , 0.5 , 1)% , Whereas lower concentrations showed a reduction of colony diameters with the increasing concentration